Designing Visual Aid - Karimova Shohida Kuvondikovna; Botirova Hakima (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Designing visual aids are essential for informed decision making. Unfortunately, many people struggle to understand typical risk communications because they lack essential decision-making skills. Objective The aim of this study was to review the literature on the effect of numeracy on risk literacy, decision making, and health outcomes, and to evaluate the benefits of visual aids in risk communication. Method We present a conceptual framework describing the influence of numeracy on risk literacy, decision making, and health outcomes, followed by a systematic review of the benefits of visual aids in risk communication for people with different levels of numeracy and graph literacy. The systematic review covers scientific research published between January 1995 and April 2016, drawn from the following databases: Improvements in risk understanding consistently produced beneficial changes in attitudes, behavioral intentions, trust, and healthy behaviors. Visual aids were found to be particularly beneficial for vulnerable and less skilled individuals.